The i-viewT M Video Laryngoscope - the Most Recent of all Video Laryngoscopes: An Observational study Analysing Performance - Habib, S Kamran; Tauheed, Nazia; Hashmi, S. Zafer (Academia Anesthesiologica International, 2020)
Background: The spectrum of video laryngoscopes appears ever-expanding with the advent of newer and newer devices. In a span of fewer than 20 years, beginning with the first device, the Glidescope in 2001, plenty of devices are now at our disposal. The i-viewT M video laryngoscope, the most recent introduction to the family in 2018, has not reportedly been evaluated yet for its performance. The objective is to evaluate the performance of the i-view video laryngoscope in terms of intubation characteristics, a prospective observational study. Subjects and Methods: The study included 60 patients undergoing laryngoscopy and intubation using the i-view video laryngoscope for nonemergency surgery requiring general anaesthesia. The primary outcome was intubation time. Modified Cormack-Lehane (CL) view, adjustment maneuvers and hemodynamic responses were also noted as secondary outcome measures. Results: Sixty patients were enrolled in the study. After exclusions, 56 patients underwent video laryngoscopy with the device. The mean intubation time was 30.3 5.1 seconds. Thirty-seven patients (66.07%) had a CL view 1, and 17 patients (30.35%) 2a. Forty patients were intubated without any adjustment maneuver, 12 needed one adjustment and 2 patients needed 2 maneuvers. There were 2 cases of failed intubation even in three attempts. The variations in haemodynamic parameters were found to be statistically insignificant. No complication related to the device could be documented. Conclusions: The new video laryngoscope, i-view is found to be at least at par with its older congeners, if not better. Larger, multicentric, comparative trials may be needed to establish the same.